ANALISIS PERPUTARAN KAS PADA PT RAYA BUMI NUSANTARA PERMAI - Elin Nurfina; Wasti Reviandani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Cash is one of the benchmarks for a company. PT Raya Bumi Nusantara Permai is a company engaged in the property sector. This research was conducted to analyze and determine the cash turnover that occurs at PT Raya Bumi Nusantara Permai, where this type of research is qualitative with a descriptive approach. The analysis technique carried out by analyze the cash turnover is using the cash trunover analysis technique. the data collection technique used is by using existing data in the financial statements of PT Raya Bumi Nusantara Permai. Based on calculation of cash flow analysis, cash turnover results at PT Raya Bumi Nusantara Permai for the priode 2016-2020 from year to year there were fluctuations in cash turnover. PT Raya Bumi Nusantara Permai when viewed from industry standards is very good value, because the turnover that can exceed ten times every year. can be concluded that cash turnover PT Raya Bumi Nusantara Permai from year to year has a different cash turnover, as thecash turnover can be seen in 2016 cash turover decreased by 18.60 times. in 2017 cash turnover of PT Raya Bumi Nusantara Permai began to increase by 29.64 times with a difference of 8.04 it could be said that the cash turnover wa of good value. and the third and fourth years, namely 2018 and 2019 cash turnover experienced a considerable increase of 46.27 times with a difference of 16.63 and cash turnover of 56.69 times with a difference of 10.42 this can be considered very god for its cash turnover. while in 2020 cash turnover suddenly descreased drastically by 18.17 times with a difference of 38.52.